2009
DOI: 10.1007/s12529-009-9057-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Non-Face-to-Face Behavioral Weight-Control Program Among Japanese Overweight Males: A Randomized Controlled Trial

Abstract: Weight loss effects of KTP were significant at 1 month, walking steps increase was maintained for 7 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 9 publications
(12 reference statements)
1
63
0
Order By: Relevance
“…Four studies were excluded because the control group received an intervention with technology aspect (Carter, Burley, Nykjaer, & Cade, 2013;Laing et al, 2014;Shaw et al, 2013;Steinberg, Levine, Askew, Foley, & Bennett, 2013). Twenty-seven trials met inclusion criteria (Agras, Taylor, Feldman, Losch, & Burnett, 1990;Allen, Stephens, Dennison Himmelfarb, Stewart, & Hauck, 2013;Appel et al, 2011;Blomfield et al, 2014;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Collins et al, 2012;Donaldson, Fallows, & Morris, 2014;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen, Tran, Wyatt, Barry, & Hill, 2007;Herring, Cruice, Bennett, Davey, & Foster, 2014;Hutchesson et al, 2014;Jeffery et al, 2003;Johnston, Massey, & DeVaneaux, 2012;Lin et al, 2014;Luley, Blaik, Reschke, Klose, & Westphal, 2011;Mehring et al, 2013;Morgan, Lubans, Collins, Warren, & Callister, 2011;Napolitano, Hayes, Bennett, Ives, & Foster, 2013;Norman, Kolodziejczyk, Adams, Patrick, & Marshall, 2013;Sherwood et al, 2006;Sherwood, Jeffery, Welsh, Vanwormer, & Hotop, 2010;Shuger et al, 2011;Svetkey et al, 2008;Tanaka, Adachi, Adachi, & Sato, 2010) and were included in this review. The total study selection process is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were excluded because the control group received an intervention with technology aspect (Carter, Burley, Nykjaer, & Cade, 2013;Laing et al, 2014;Shaw et al, 2013;Steinberg, Levine, Askew, Foley, & Bennett, 2013). Twenty-seven trials met inclusion criteria (Agras, Taylor, Feldman, Losch, & Burnett, 1990;Allen, Stephens, Dennison Himmelfarb, Stewart, & Hauck, 2013;Appel et al, 2011;Blomfield et al, 2014;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Collins et al, 2012;Donaldson, Fallows, & Morris, 2014;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen, Tran, Wyatt, Barry, & Hill, 2007;Herring, Cruice, Bennett, Davey, & Foster, 2014;Hutchesson et al, 2014;Jeffery et al, 2003;Johnston, Massey, & DeVaneaux, 2012;Lin et al, 2014;Luley, Blaik, Reschke, Klose, & Westphal, 2011;Mehring et al, 2013;Morgan, Lubans, Collins, Warren, & Callister, 2011;Napolitano, Hayes, Bennett, Ives, & Foster, 2013;Norman, Kolodziejczyk, Adams, Patrick, & Marshall, 2013;Sherwood et al, 2006;Sherwood, Jeffery, Welsh, Vanwormer, & Hotop, 2010;Shuger et al, 2011;Svetkey et al, 2008;Tanaka, Adachi, Adachi, & Sato, 2010) and were included in this review. The total study selection process is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Most studies were conducted in the United States of America (N ¼ 18) (Agras et al, 1990;Allen et al, 2013;Appel et al, 2011;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen et al, 2007;Herring Jeffery et al, 2003;Johnston et al, 2012;Napolitano et al, 2013;Norman et al, 2013;Sherwood et al, 2006Sherwood et al, , 2010Shuger et al, 2011;Svetkey et al, 2008). Four studies were conducted in Australia (Blomfield et al, 2014;Collins et al, 2012;Hutchesson et al, 2014;Morgan et al, 2011), one study in China (Lin et al, 2014), one study in Japan (Tanaka et al, 2010), one study in the United Kingdom (Donaldson et al, 2014) and two studies in Germany (Luley et al, 2011;Mehring et al, 2013). The study populations consisted of overweight or obese adults.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…age and BMI were 46 (±6) years and 32 (±3) kg m À2 , respectively. Of the 22 studies that provided the study-specific minimum BMI to define overweight or obesity, the value was X25 kg m À2 to o 30 kg m À2 except in three studies 26,35,38 that used a BMI o25 kg m À2 cut-off value for being overweight and three studies 28,32,36 that exclusively targeted participants with a BMI X30 kg m À2 . Most of the studies (17 studies) used an intent-to-treat analysis.…”
Section: Data Synthesismentioning
confidence: 99%
“…Table 2 shows details of the obesity treatment programs in each included study. To summarize the study-specific Webbased programs in terms of the role of the Internet, 16 studies [18][19][20][23][24][26][27][28][30][31][33][34][35][36][38][39] used the Internet as an adjunct to the non-Web-based obesity care support provided in both control and experimental groups. One study 25 used it as a substitute for face-to-face counseling.…”
Section: Data Synthesismentioning
confidence: 99%